Insight and Artistry in African Divination - Pemberton, John (Smithsonian, 2000)
Among the peoples of Central and West Africa, artifacts such as sculptures, trays, baskets, animal horns, rubbing devices, and slit-drums are essential to the efficacy of divination rituals, attempts by individuals, families, or communities to discern through diviners the causes and meaning of anxiety, mishaps, conflicts, losses, and death. Although such instruments need only be rudimentary for the ritual to be performed, the aesthetic power of ritual objects that are created with imagination and skill enhances their ability to convey meaning. Generously illustrated, this volume demonstrates that ritual objects contribute to the purpose of divinatory rituals—and that for the peoples of sub-Saharan Africa, insight and artistry are inextricably related.
free